PELUANG DAN TANTANGAN PENYIMPANAN CLOUD STORAGE PADA DOKUMEN DIGITAL - Lisy Tantowi; Luki Wijayanti (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2023)
Cloud storage is a digital document storage application which is the result of the development of a cloud computing system, this system utilizes the internet network in carrying out its business processes. Utilization of cloud storage applications on digital documents provides various conveniences for users, not only professional users who work for their organizations but can be used by individual personal users who use it to store personal documents. With the existence of a remote work system must be implemented, in disruption era which is slowly shifting conventional patterns, it also affects the process of storing digital documents into things that need to be implemented in organizations. Cloud storage supports collaboration which is easy to implement with colleagues, access can be done anywhere and anytime, to have advanced security. Online document storage provides benefits for business processes. The benefits of cloud storage are supporting paperless programs, making it easier to preserve digital documents, helping organizations in controlling data, mitigating disasters against unpredictable events, saving expenses, and having an advanced data security system. In addition to the benefits/conveniences offered by the service provider. User readiness needs to be considered. This will be a challenge aspect in implementing cloud storage, such as education and socialization regarding the use of cloud storage systems which are still not optimal, vulnerabilities in the misuse of document data stored in the cloud and requires superior human resources in the use of cloud storage.